1986
DOI: 10.1111/j.1471-6402.1986.tb00765.x
|View full text |Cite
|
Sign up to set email alerts
|

Gender Bias in Human Anatomy Textbook Illustrations

Abstract: The hypothesis that female and male bodies are equally represented in human anatomy text illustrations was tested to determine whether medical students are shown both females and males as possessing equally important and normal bodies in medical school instructional material. All anatomy texts currently in use in a major western medical school (N = 8) were surveyed. In text sections dealing with standard (non‐gender‐specific) anatomy, male subjects were shown in 64% of the illustrations in which gender was dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 7 publications
6
28
0
Order By: Relevance
“…However, such studies have focused mainly on anatomy textbooks. The results of these investigations agree unanimously with the previously mentioned findings for education in general, that is, they demonstrate that medical textbooks also tend to show strong gender bias in regard to contents, illustrations, language (Scully et al, 1973;Giacomini et al, 1986;Lawrence et al, 1992;Mendelsohn et al, 1994), and references (Forsberg et al, 1996). The male anatomy is often presented as the norm for ''the'' human, whereas the female counterpart, if referred to at all, is mentioned as an exception or as abnormal (Mendelsohn et al, 1994).…”
Section: Textbookssupporting
confidence: 79%
See 1 more Smart Citation
“…However, such studies have focused mainly on anatomy textbooks. The results of these investigations agree unanimously with the previously mentioned findings for education in general, that is, they demonstrate that medical textbooks also tend to show strong gender bias in regard to contents, illustrations, language (Scully et al, 1973;Giacomini et al, 1986;Lawrence et al, 1992;Mendelsohn et al, 1994), and references (Forsberg et al, 1996). The male anatomy is often presented as the norm for ''the'' human, whereas the female counterpart, if referred to at all, is mentioned as an exception or as abnormal (Mendelsohn et al, 1994).…”
Section: Textbookssupporting
confidence: 79%
“…To date, only a few studies have analyzed medical textbooks from a gender perspective, and those have focused primarily on anatomy books and the extent to which data (text or illustrations) about women are included and whether such data are presented as exceptions (Scully et al, 1973;Giacomini et al, 1986;Lawrence et al, 1992;Mendelsohn et al, 1994). The assessment protocol developed in the present study was found to facilitate more comprehensive gender analysis of textbooks.…”
Section: Discussionmentioning
confidence: 97%
“…These results compare with studies of medical (and general) education materials, such as anatomy and other texts that demonstrate a gender bias. 25,26,31,32,33,40 The findings demonstrate not only a majority of male images but also of white images, which has not previously been formally studied in the medical curriculum. While some earlier studies excluded reproductive focused materials out of concern that the emphasis on female subject material would skew the sample, this study included reproductive and other female focused subject matter and nevertheless discovered a majority of male images.…”
Section: Discussionmentioning
confidence: 76%
“…Women appear to suffer more negative health consequences of inequalities between the sexes. The very recent increase in research on sex and gender differences, with it's focus on women, has begun to correct a history of generalization from the male subject to the female population [11-13]. Government funding agencies have given priority to research in women's health in recent decades to correct these past imbalances in research.…”
Section: Differentiating Gender and Women's Healthmentioning
confidence: 99%